The Operation Python Dance of the Nigeria Military on South Eastern Nigeria: Causes, Public Perception, Youth Protest, and Impact 2016-2023 - Chukwuemeka, Gold; Paul Oshagwu Opone (Advances in Humanities and Contemporary Studies, 2025)
The Operation Python Dance of the Nigeria Military, still lingers around the South Eastern Nigeria, as a contended and contested military excursion with far-reaching impact on the region. That’s how the security issue evolved and later turned into outright confrontation between the Nigerian military and the locals. The paper demonstrates, through both analytical and historical methods of research, that new paths toward reconciliation and lasting peace can ultimately be forged by a revitalized and more balanced approach. The paper concludes that the Federal Government of Nigeria should give its attention to the perceived marginalization of the region in its efforts to ensure sustainable security.